AB0430 Effects of Abatacept and TNF Inhibitors Compared with Ultrasonography in Patients with Rheumatoid Arthritis. (10th June 2014) - Mamoto, K.; Koike, T.; Okano, T.; Sugioka, Y.; Tada, M.; Inui, K.; Nakamura, H.
Abstract : Objectives: The present study aimed to compare the effects of abatacept (ABT) and tumor necrosis factor inhibitors (TNFi) against rheumatoid arthritis (RA). Methods: Patients with RA were treated with ABT (n=51) or TNFi (n=89; adalimumab, n=35; etanercept n=23; infliximab n=15; golimumab n=16). Twenty-six synovial sites comprising 22 joints (bilateral first to fifth metacarpophalangeal (dorsal recess), first interphalangeal and second to fifth proximal interphalangeal (dorsal recess) joints and dorsal radial, dorsal median and dorsal ulnar parts of the wrists) were assessed by musculoskeletal ultrasonography. Gray scale and power Doppler signals in these joints were semi-quantified using a scale from 0 to 3. We then compared disease activity, 28-CRP (DAS) scores and the sum of GSUS and PDUS scores between the two groups. Results: The DAS score was significantly lower after two months of TNFi treatment compared with baseline, but did not significantly improve compared with baseline in the ABT group at two months. The DAS scores were lower for the TNFi than for the ABT group at six and eight months, but did not significantly differ at 12 months (Fig. 1 ). The sums of the GSUS and PDUS scores at 12 months were lower than those at baseline in both groups; however, these differences were not significant. Conclusions: The clinical effect of ABT was slower than that of TNFi, but matched those of TNFi at 12 months. The effects of ABT and TNFi were similar according to ultrasound assessment. Disclosure of Interest: K. Mamoto: None declared, T. Koike Grant/research support: Takeda Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Chugai Pharmaceutical, Eisai, Abbott Japan, Teijin Pharma, Banyu Pharmaceutical and Ono Pharmaceutical, T. Okano: None declared, Y. Sugioka: None declared, M. Tada: None declared, K. Inui Grant/research support: Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Astellas Pharma Inc., Abbvie GK, Eisai Co., Ltd., MSD K.K. Speakers bureau: Bristol-Myers K.K., Takeda Pharmaceutical Corporation, Ltd., Chugai Pharmaceutical Co., Ltd., Janssen Pharmaceutical K.K., Abbvie GK, Astellas Pharma Inc., H. Nakamura Grant/research support: Chugai Pharmaceutical Co., Ltd., Astellas Pharma Inc., Nippon Zoki Pharmaceutical Co., Ltd., Daiichi Sankyo Speakers bureau: Eisai Co., Ltd., Daiichi Sankyo DOI: 10.1136/annrheumdis-2014-eular.3222